The Paradox of Organizational Behavior in Command Institutions: A Critical Study of Obedience, Integrity, and Loyalty in the Indonesian National Police - Rissan Simaremare; Rini Rahmawati; Ahmad Rifani (International Journal of Business and Quality Research, 2025)
This study critically examines the paradox of obedience within the Indonesian National Police (Polri), a command-based institution where hierarchical discipline, loyalty, and ethical conduct are often in tension. Drawing on 25 in-depth interviews with police officers and community members, and supported by document analysis, the research explores how institutional structures and leadership cultures shape behaviors related to moral disengagement, organizational silence, and vertical loyalty. Using a qualitative case study approach under an interpretivist paradigm, thematic coding was conducted with NVivo software to identify five dominant patterns: (1) imperative hierarchical obedience, (2) loyalty to superiors over institutional values, (3) systemic erosion of personal integrity, (4) fear-driven organizational silence, and (5) bifurcated public perceptions of institutional legitimacy. The findings reveal that obedience is frequently decoupled from moral judgment, transforming into an instrument of structural control that suppresses dissent and rewards conformity. Moreover, loyalty—while fostering cohesion—can enable permissive cultures that rationalize unethical conduct when not grounded in institutional ethics. The study offers a conceptual model linking obedience, loyalty, and silence as a behavioral continuum, which, if left unmoderated by ethical leadership and institutional integrity, results in normalized moral disengagement. This paper contributes theoretically to the discourse on command institutions by reframing obedience as an ethical condition shaped by organizational design, not merely individual will. It also provides practical insights for reforming policing culture through leadership training, whistleblower protection, and integrity-based accountability frameworks.